PENERAPAN METODE SAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DIKELAS I SDN 079/II BARU PUSAT JALO - Dani, Refril; Aprizan, Aprizan; Maulana Putra, Ikhsan; Arsita, Cindy (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
The low ability of students in class I SDN 079/II Pusat Jalo, Bungo Regency, Jambi Province in reading the beginning is the background for the research, where there are 15 students in 1 class, where they still find it difficult to read the beginning. It aims to improve the ability to read the beginning as seen from the process and results of reading the beginning of class one students of SDN 079/II Pusat Jalo with Structural Analytical Synthetic as the method. The type of research used is Classroom Action Research, consisting of two cycles, each cycle consisting of planning activities, implementation of actions, observation, and reflection. the subjects of this study were class one, namely one teacher and 15 students at SDN 079/II Pusat Jalo. The results of this study show that teachers in the learning process, cycle one first meeting 69%, cycle one second meeting increased to 75%. Furthermore, cycle two first meetings, and the second teacher process increased again to 100%. The student process during the learning process in cycle one first meeting 68%, cycle one second meeting increased to 74% said not to have been achieved. In the second cycle, the first meeting increased to 79%, in the second cycle, the second meeting increased again to 82% and it was said to have been achieved. The results of the observation of the assessment of the initial reading test of students in cycle one that was achieved were only 9 students or 60%, who were achieved. In the second cycle, 13 students or 91% were achieved and declared successful.